Reações redox catalisadas por complexos de cobre derivados de bases de Schiff: impactos do estado de oxidação e do ligante - Castro, Caio Bezerra de (Universidade Federal de São Carlos, 2023)
In this work, two series of Cu2+ complexes with Schiff base ligands derived from the amino acid L-Proline were synthesized and characterized, which are tridentate N,N,O (series 1) and tetradentate N,N,N,O (series 2). The complexes were applied in redox catalysis involving the transfer of protons and electrons using Nitrogenases as an inspirational model metalloenzyme. These enzymes have high reductive capacity due to metal ions in the active site that have easy modulation of the redox state and a strategically positioned network of amino acids active in proton transfer. In this regard, Cu2+ complexes act as functional mimetics, as they do not have structural similarity in relation to the active site of these metalloenzymes, but they can have a similar catalytic function. Two reactions were used as a study platform: the reductions of the substrates 1-azido-4-nitrobenzene to 1-amino-4-nitrobenzene and carbon dioxide. During the work, it was observed that the Cu2+ complexes were reduced to Cu1+ by the addition of sodium ascorbate as a sacrificial reducing agent in acetonitrile only, while the use of methanol as a reaction solvent did not allow the in situ reduction of the complexes. This behavior directly affected the catalytic performance of the complexes, as in the aprotic organic solvent a maximum value of TON = 6 was obtained while in the protic organic solvent TON values between 16 and 72 were obtained. Analysis of the reaction by Electronic Paramagnetic Spectroscopy at 77 K in methanol showed the presence of the Cu2+-phenoxyl species and studies with DMPO as a spin trap at 298 K showed the formation of the ascorbyl radical that remains in solution throughout the reaction, corroborating the radical reaction from the transfer of electrons from ascorbate to the azide substrate. The same complexes were also evaluated for reducing carbon dioxide, which were active only via the electrochemical route. The non-innocent redox nature of the ligands was relevant for the catalytic performance of the complexes, where a Metal-Assisted-Ligand-Centered reactivity was observed. From voltammetric studies, the TOFmax value was calculated to be 746 s-1 for the Cu2HP complex, considered the best catalyst. From Electrolysis under Controlled Potential it was possible to identify and quantify some reduction products such as HCOO- (format), CH3COOH (acetic acid) and CH3CH(OH)2 (hydrolyzed acetaldehyde) by analyzing the liquid fraction by 1H and 13C NMR and H2 (hydrogen) and CO (carbon monoxide) analyzing the gaseous fraction by GC-BID.
Redox reactions catalyzed by copper complexes derived from Schiff bases: impacts of oxidation state and ligand
Keywords: Redução eletroquímica do CO2; Redução molecular de azidas orgânicas; Geração de Aminas orgânicas; Ligantes bases de Schiff; Complexos de Cu2+; Mimetismo funcional; Electrochemical CO2 reduction; Molecular reduction of organic azides; Generation or organic amines; Schiff base ligands; Cu2+ complexes; Functional mimicry; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA